Characterization of biofilm and coagulase producing Staphylococcus aureus associated with bovine mastitis - MANKAR, DIPIKA; GANDGE, RAJASHREE; BANNALIKAR, ANILKUMAR (The Indian Journal of Animal Sciences, 2015)
Present research was planned to study incidence, virulence factors viz. biofilm and coagulase production and antibiogram of Staphylococcus aureus associated with bovine mastitis. Milk samples (142) of clinical and subclinical bovine mastitis cases from Mumbai and around Mumbai region were processed. From the milk samples processed; 52 (36.61%) Staphylococcus spp. isolates were recovered. Incidence of S. aureus in bovine mastitis was 28.16% (in cows: 41.37% and in buffaloes: 24.77%). The incidence rate of S. aureus in subclinical and clinical mastitis was 17.24% and 30.97% respectively. The results of antibiotic resistance pattern of isolates indicated highest resistance to penicillin (100%) followed by vancomycin and oxacillin (77.5%) and gentamicin (15%). The least resistance was observed to chloramphenicol (12.5%), ceftriaxone (10%), methicillin and cephotaxim (7.5%). Out of 40 S. aureus isolates characterized for biofilm production, overall 32 (80%) isolates were biofilm producing which were confirmed using various methods, viz. CRA (45%), TCP (35%) and PCR (72.5%) of intercellular adhesin gene ica A and ica D. Of 32 biofilm producing S. aureus, 20 (62.50%) were coagulase producing strains and 65.62% of them also showed biofilm production. Out of 40 S. aureus isolates, 26 (65.00 %) were proved to be coagulase producing strains by tube method; whereas by coa PCR assay, 21 (52.5%) isolates showed presence of coagulase gene. Out of 21 coa exhibiting strains of S. aureus, 4 (10%) isolates were of coa genotype A with an amplicon size of 850 bp while 17 (42.5%) S. aureus isolates were of genotype B with an amplicon product of 600 bp. Out of 26 coagulase producing S. aureus, 21 (80.76%) were biofilm producing. Most of biofilm and coagulase producing strains displayed multiple drug resistant.